#### Answer

-5

#### Work Step by Step

As shown on page 437, $\sqrt[n] a^{n}=|a|$ when $n$ is an even positive integer.
Therefore, we know that $\sqrt[6] (-5)^{6}=|-5|=5$.
As a result, $-\sqrt[6] (-5)^{6}=-(5)=-5$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-5

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.